Body Composition and Somatotype Profiles of Rowers - Kürşat Acar; Erkal Arslanoğlu; Ahmet Mor; Kadir Baynaz; Gökhan İpekoğlu; Cansel Arslanoğlu (Selcuk University, 2020)
Purpose: The aim of this study was to examine the body composition and somatotype profiles of rowers. Method: 15 male rowers having at least 4 years rowing training from two different rowing clubs in Sinop participated voluntarily in this study. In athletes, conditions such as being healthy, not having chronic or acute disease and having no limitation of mobility were sought. In body 120 Body Composition Analyzer was used to assess the body composition components and Skinfold caliper-tape measurement was used to determine somatotype profiles. Mean and standard deviations of the participants were calculated by using SPSS 22.0 V. package program. Results: Mean values of body composition of the rowers were respectively; body fat ratio %15.94±6.84, body fat mass 11.73±5.76 kg, skeletal body mass 34.207±5.98 kg, basal metabolic rate 1674±211.65 kcal and total body water 44.36±7.10 lt. Somatotype profiles values of athletes were found endomorph 2.01±0.71, mesomorph 4.75±0.82 and ectomorph 2.70±0.71 body type. Conclusion: This study supports that rowers have the body composition proportional to the normal fat percentage and the mesomorph body type associated with high muscle strength as somatotype.